A REVIEW OF AUDIT DEVELOPMENTS IN IRAN - Tasaddi Kari, Mohammad Javad; Azadi Hir, Keyhan; Rezazadeh, Javad; Kheradyar, Sina (Department of Accounting, Faculty of Economics & Business, Universitas Diponegoro, 2023)
Considering the role and importance of the auditing profession, the present research has reviewed the developments of auditing and finding the root causes of its lack of development in Iran. After studying the relevant research literature and identifying the factors affecting the development of audit services at the international level, the root cause of this backwardness was investigated. The results show that the role of Limperg's Dynamic Theory, Legal Requirements of Mautz and Sharaf, and Adam Smith's Theory of Division of Labor are effective on this issue. Also, the development of international trade, the formation of online work teams, sanctions, advertising; Creating a demand for auditing services, establishing standards and regulatory laws, requiring the development of various skills, forming institutions that establish, implement and oversee various services; Benefiting from expert forces in various sciences, development of human knowledge, etc., can lead to the development of the assurance services market.